Nanoarchitectonics of the cathode to improve the reversibility of Li–O2 batteries - Pham, Hien Thi Thu; Yun, Jonghyeok; Kim, So Yeun; Han, Sang A; Kim, Jung Ho; Lee, Jong-Won; Park, Min-Sik (Beilstein Journal of Nanotechnology, 2022)
The strategic design of the cathode is a critical feature for high-performance and long-lasting reversibility of an energy storage system. In particular, the round-trip efficiency and cycling performance of nonaqueous lithium–oxygen batteries are governed by minimizing the discharge products, such as Li2O and Li2O2. Recently, a metal–organic framework has been directly pyrolyzed into a carbon frame with controllable pore volume and size. Furthermore, selective metallic catalysts can also be obtained by adjusting metal ions for outstanding electrochemical reactions. In this study, various bimetallic zeolitic imidazolate framework (ZIF)-derived carbons were designed by varying the ratio of Zn to Co ions. Moreover, carbon nanotubes (CNTs) are added to improve the electrical conductivity further, ultimately leading to better electrochemical stability in the cathode. As a result, the optimized bimetallic ZIF–carbon/CNT composite exhibits a high discharge capacity of 16,000 mAh·g−1, with a stable cycling performance of up to 137 cycles. This feature is also beneficial for lowering the overpotential of the cathode during cycling, even at the high current density of 2,000 mA·g−1.
Keywords: cathode composition; electrochemistry; Li–O2 battery; metal–organic framework; nanoarchitectonics; zeolitic imidazolate framework

(untitled) - Grande, L.; Paillard, E.; Hassoun, J.; Park, J.-B.; Lee, Y.-J.; Sun, Y.-K.; Passerini, S.; Scrosati, B. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Aurbach, D.; McCloskey, B. D.; Nazar, L. F.; Bruce, P. G. (Nat. Energy, 2016)

(untitled) - Lu, Y.-C.; Gallant, B. M.; Kwabi, D. G.; Harding, J. R.; Mitchell, R. R.; Whittingham, M. S.; Shao-Horn, Y. (Energy Environ. Sci., 2013)

(untitled) - Padbury, R.; Zhang, X. (J. Power Sources, 2011)

(untitled) - Geng, D.; Ding, N.; Hor, T. S. A.; Chien, S. W.; Liu, Z.; Wuu, D.; Sun, X.; Zong, Y. (Adv. Energy Mater., 2016)

(untitled) - Balaish, M.; Jung, J.-W.; Kim, I.-D.; Ein‐Eli, Y. (Adv. Funct. Mater., 2020)

(untitled) - Zhai, D.; Wang, H.-H.; Yang, J.; Lau, K. C.; Li, K.; Amine, K.; Curtiss, L. A. (J. Am. Chem. Soc., 2013)

(untitled) - Zhou, Y.; Zhao, Y.; Liu, Z.; Peng, Z.; Wang, L.; Chen, W. (J. Energy Chem., 2021)

(untitled) - Black, R.; Oh, S. H.; Lee, J.-H.; Yim, T.; Adams, B.; Nazar, L. F. (J. Am. Chem. Soc., 2012)

(untitled) - Wong, R. A.; Dutta, A.; Yang, C.; Yamanaka, K.; Ohta, T.; Nakao, A.; Waki, K.; Byon, H. R. (Chem. Mater., 2016)

(untitled) - Jung, J.-W.; Cho, S.-H.; Nam, J. S.; Kim, I.-D. (Energy Storage Mater., 2020)

(untitled) - Pham, H. T. T.; Choi, Y.; Park, M.-S.; Lee, J.-W. (Chem. Commun., 2020)

(untitled) - Ottakam Thotiyl, M. M.; Freunberger, S. A.; Peng, Z.; Bruce, P. G. (J. Am. Chem. Soc., 2013)

(untitled) - Geng, H.; Peng, Y.; Qu, L.; Zhang, H.; Wu, M. (Adv. Energy Mater., 2020)

(untitled) - Kichambare, P.; Kumar, J.; Rodrigues, S.; Kumar, B. (J. Power Sources, 2011)

(untitled) - Shui, J.; Lin, Y.; Connell, J. W.; Xu, J.; Fan, X.; Dai, L. (ACS Energy Lett., 2016)

(untitled) - Yang, M.; Zhou, Y.-N.; Cao, Y.-N.; Tong, Z.; Dong, B.; Chai, Y.-M. (Appl. Mater. Today, 2020)

(untitled) - Wen, X.; Guan, J. (Appl. Mater. Today, 2019)

(untitled) - Liao, Y.-T.; Nguyen, V. C.; Ishiguro, N.; Young, A. P.; Tsung, C.-K.; Wu, K. C.-W. (Appl. Catal., B, 2020)

(untitled) - Yang, R.-X.; Bieh, Y.-T.; Chen, C. H.; Hsu, C.-Y.; Kato, Y.; Yamamoto, H.; Tsung, C.-K.; Wu, K. C.-W. (ACS Sustainable Chem. Eng., 2021)

(untitled) - Konnerth, H.; Matsagar, B. M.; Chen, S. S.; Prechtl, M. H. G.; Shieh, F.-K.; Wu, K. C.-W. (Coord. Chem. Rev., 2020)

(untitled) - Chueh, C.-C.; Chen, C.-I.; Su, Y.-A.; Konnerth, H.; Gu, Y.-J.; Kung, C.-W.; Wu, K. C.-W. (J. Mater. Chem. A, 2019)

(untitled) - Liu, Y.-C.; Yeh, L.-H.; Zheng, M.-J.; Wu, K. C.-W. (Sci. Adv., 2021)

(untitled) - Ge, L.; Yang, Y.; Wang, L.; Zhou, W.; De Marco, R.; Chen, Z.; Zou, J.; Zhu, Z. (Carbon, 2015)

(untitled) - Chen, K.; Sun, Z.; Fang, R.; Shi, Y.; Cheng, H.-M.; Li, F. (Adv. Funct. Mater., 2018)

(untitled) - Sun, X.; Olivos-Suarez, A. I.; Osadchii, D.; Romero, M. J. V.; Kapteijn, F.; Gascon, J. (J. Catal., 2018)

(untitled) - Bhadra, B. N.; Vinu, A.; Serre, C.; Jhung, S. H. (Mater. Today, 2019)

(untitled) - Chen, Y.-Z.; Wang, C.; Wu, Z.-Y.; Xiong, Y.; Xu, Q.; Yu, S.-H.; Jiang, H.-L. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Bhadra, B. N.; Khan, N. A.; Jhung, S. H. (J. Mater. Chem. A, 2019)

(untitled) - Qutaish, H.; Lee, J.; Hyeon, Y.; Han, S. A.; Lee, I.-H.; Heo, Y.-U.; Whang, D.; Moon, J.; Park, M.-S.; Kim, J. H. (Appl. Surf. Sci., 2021)

(untitled) - Lee, J.; Park, M.-S.; Kim, J. H. (Nano Convergence, 2021)

(untitled) - Lee, J.; Choi, S. H.; Qutaish, H.; Hyeon, Y.; Han, S. A.; Heo, Y.-U.; Whang, D.; Lee, J.-W.; Moon, J.; Park, M.-S.; Kim, J. H.; Dou, S. X. (Energy Storage Mater., 2021)

(untitled) - Hyeon, Y.; Lee, J.; Qutaish, H.; Han, S. A.; Choi, S. H.; Moon, S. W.; Park, M.-S.; Whang, D.; Kim, J. H. (Energy Storage Mater., 2020)

(untitled) - Choi, S. H.; Hyeon, Y.; Shin, H. R.; Eom, G. H.; Pham, H. T. T.; Whang, D.; Kim, S. Y.; Lee, J.-W.; Kim, J. H.; Park, M.-S. (Nano Energy, 2021)

(untitled) - Han, S. A.; Lee, J.; Shim, K.; Lin, J.; Shahabuddin, M.; Lee, J.-W.; Kim, S.-W.; Park, M.-S.; Kim, J. H. (Bull. Chem. Soc. Jpn., 2018)

(untitled) - Wang, Y.; Wang, J.; Mohamed, Z.; Huang, Q.; Chen, T.; Hou, Y.; Dang, F.; Zhang, W.; Wang, H. (Appl. Mater. Today, 2020)

(untitled) - Cao, D.-Q.; Wang, Q.-Z.; Yin, X.; Sun, Y.-D.; Ma, M.; Wu, Y.-P.; Liu, X.-J. (Energy Fuels, 2020)

(untitled) - Zhao, Y.; Ding, L.; Wang, X.; Yang, X.; He, J.; Yang, B.; Wang, B.; Zhang, D.; Li, Z. (J. Alloys Compd., 2021)

(untitled) - Saliba, D.; Ammar, M.; Rammal, M.; Al-Ghoul, M.; Hmadeh, M. (J. Am. Chem. Soc., 2018)

(untitled) - Jung, K.-N.; Kim, J.; Yamauchi, Y.; Park, M.-S.; Lee, J.-W.; Kim, J. H. (J. Mater. Chem. A, 2016)

(untitled) - Pham, H. T. T.; Kim, Y.; Kim, Y.-J.; Lee, J.-W.; Park, M.-S. (Adv. Funct. Mater., 2019)